The rodent models of arteriovenous fistula - Li, Yuxuan; Hu, Ke; Li, Yiqing; Lu, Chanjun; Guo, Yi; Wang, Weici (Frontiers in Cardiovascular Medicine, 2024)
Arteriovenous fistulas (AVFs) have long been used as dialysis access in patients with end-stage renal disease; however, their maturation and long-term patency still fall short of clinical needs. Rodent models are irreplaceable to facilitate the study of mechanisms and provide reliable insights into clinical problems. The ideal rodent AVF model recapitulates the major features and pathology of human disease as closely as possible, and pre-induction of the uremic milieu is an important addition to AVF failure studies. Herein, we review different surgical methods used so far to create AVF in rodents, including surgical suturing, needle puncture, and the cuff technique. We also summarize commonly used evaluations after AVF placement. The aim was to provide recent advances and ideas for better selection and induction of rodent AVF models. At the same time, further improvements in the models and a deeper understanding of AVF failure mechanisms are expected.